2018
DOI: 10.1007/978-3-319-95174-4_52
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Residential Water Consumption Determinants

Abstract: Abstract. Water supply sectors are facing higher uncertainty in both resource availability and consumer demand. Future conservation programs require a full understanding of underlying factors of residential water consumption. However, previous studies have only considered one or several groups of factors without putting them all together in a bigger picture. This study was developed to provide a comprehensive view on these determinants and their relationships, as well as to discuss current gaps and possible di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 54 publications
(130 reference statements)
0
26
0
1
Order By: Relevance
“…Several studies have been undertaken to understand the effect of socioeconomic and demographic factors in water consumption and conservation [19,32,94]. Although these studies have not promoted immediate water savings, they have helped to identify the social, economic, and demographic factors behind water consumption patterns, which may lead to effective water management policies such as targeted community awareness programs or education.…”
Section: Socioeconomic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been undertaken to understand the effect of socioeconomic and demographic factors in water consumption and conservation [19,32,94]. Although these studies have not promoted immediate water savings, they have helped to identify the social, economic, and demographic factors behind water consumption patterns, which may lead to effective water management policies such as targeted community awareness programs or education.…”
Section: Socioeconomic Analysismentioning
confidence: 99%
“…In addition, studies performed to identify the determinants of household water consumption are essential for understanding the factors behind increasing or decreasing water usage. According to Bich-Ngoc and Teller [19], the examined factors in the literature can be categorised into six groups: (a) economic; (b) sociodemographic; (c) physical characteristics; (d) technological; (e) climatic; and (f) special factors. Higher income, older tenants, presence of infants, double income family, larger house area, irrigation, holiday, number of generations, and renter-occupied household are some of the drivers behind increased water consumption.…”
Section: Socioeconomic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the influence of price on domestic water consumption also differs among people of different socio-demographic groups. Literature has shown that domestic water consumption is low in low-income households since water in such households is just only for basic needs and as such cannot be reduced even with high water prices (Bich Ngoc & Teller, 2018;Inman & Jeffery, 2006) However, studies have also demonstrate that there is also evidence that very little or no effect of price to domestic water consumption on high-income households (Renwick & Archibald, 1998) since price signal is not strong enough to curb their consumption (Renwick & Green, 2000). Some studies point to the fact that water consumption is more responsive to price changes in summer than in winter.…”
Section: Water Price and Domestic Water Consumption In Karoimentioning
confidence: 99%
“…To date, however, few studies consider a long-list of potential factors of influence. They account only for one or a small number of independent variables instead, with household size and income level being frequently studied (Bich-Ngoc and Teller, 2018;Wiedenhofer et al, 2013). Still, it is known that consumption patterns cannot be explained by individual factors but rather by a large number of interconnected factors that have direct and indirect effects (Bich-Ngoc & Teller, 2018;Voskamp et al, 2020;You & Kim, 2018).…”
Section: Introductionmentioning
confidence: 99%